Afasia Broca Pada Trombosis Serebri - Elvina Zuhir (LPPM Universitas Abdurrab, 2023)
Broca's aphasia is a communication disorder commonly occurring after damage to the Broca's area in the brain. One of the conditions that can lead to such damage is cerebral thrombosis, the blockage of blood vessels in the brain by blood clots. This study aims to explore the relationship between cerebral thrombosis and the manifestation of Broca's aphasia. The research method used is a retrospective analysis of medical data from patients diagnosed with cerebralthrombosis and exhibiting symptoms of Broca's aphasia. The analyzed data include medical history, neurological examination results, brain imaging findings, and the progression of aphasia symptoms in patients. The results of the study indicate that Broca's aphasia is one of the clinical manifestations frequently observed in patients with cerebral thrombosis. The symptoms of Broca's aphasia may vary depending on the location and extent of the thrombosis-affected area.Nonetheless, a deeper understanding of this relationship can provide new insights into the management and care of patients with cerebral thrombosis experiencing communication impairments. This study highlights the importance of comprehensive management for patients with cerebral thrombosis, including careful neurological evaluation to detect aphasia symptoms and provide timely interventions.